2021
DOI: 10.3390/sym13040694
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Symmetrical and Asymmetrical Jumps and Their Influence on Speed Abilities: Gender Consideration

Abstract: Purpose: Plyometric exercises, in the form of jumping, are extreme physical activities. The aim of the study was to determine how symmetrical-single versus asymmetrical-continued plyometric exercises differ between men and women and affect speed abilities. Methods: Twenty-two healthy females and forty-four males from different sports practices participated in the investigation. The countermovement jump (CMJ) and drop jump (DJ) of 40/60 cm box were performed on two independent and synchronized force platforms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Given the high degree of heterogeneity, we had to conduct a qualitative analysis of the associations between the standing triple jump and sprint performance. Seven studies examined the associations between the standing triple jump distance and sprint time ( Habibi et al, 2010 ; Hudgins et al, 2013 ; Kale et al, 2009 ; Mackala et al, 2021 ; Maulder & Cronin, 2005 ; Maulder, Bradshaw & Keogh, 2006 ; Yanci et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the high degree of heterogeneity, we had to conduct a qualitative analysis of the associations between the standing triple jump and sprint performance. Seven studies examined the associations between the standing triple jump distance and sprint time ( Habibi et al, 2010 ; Hudgins et al, 2013 ; Kale et al, 2009 ; Mackala et al, 2021 ; Maulder & Cronin, 2005 ; Maulder, Bradshaw & Keogh, 2006 ; Yanci et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated acceleration performance ( Habibi et al, 2010 ; Mackala et al, 2021 ; Maulder & Cronin, 2005 ; Maulder, Bradshaw & Keogh, 2006 ; Yanci et al, 2014 ), while two assessed maximal speed performance ( Hudgins et al, 2013 ; Kale et al, 2009 ). In terms of acceleration, 5 m ( Yanci et al, 2014 ), 10 m ( Habibi et al, 2010 ; Mackala et al, 2021 ; Maulder, Bradshaw & Keogh, 2006 ; Yanci et al, 2014 ), 15 m ( Yanci et al, 2014 ), and 20 m ( Mackala et al, 2021 ; Maulder & Cronin, 2005 ), and 30 m ( Mackala et al, 2021 ) sprint time were evaluated in these studies. Notably, subjects included in these studies were sprinters and players from different sports backgrounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, insufficient attention is focused on defining parameters and the impact of the training program by applying a horizontal drop jump (HDJ), which has more similarities in its structure to activities dominated by horizontal movements (running, horizontal jumps). When observing correlation of vertical and horizontal jumps with sprint running over 10, 20 and 30 m, strongest correlation was determined in horizontal single leg jump, which is due to similar kinematic and dynamic structures with running gait [12]. Dobbs et al [13] compared the peak and average forces of top athletes in the performance of vertical (Peak force = 4915 N; Mean force = 2749 N) and HDJ (Peak force = 1163 N; Mean force = 528) and concluded that significantly less force is manifested in the performance of a unilateral horizontal drop jump (UHDJ).…”
Section: Introductionmentioning
confidence: 90%